Optimizing Test and Treat in Malawi: health care worker perspectives on barriers and facilitators to ART initiation among HIV-infected clients who feel healthy. Issue 1 (31st December 2020) - Dovel, Kathryn; Phiri, Khumbo; Mphande, Misheck; Mindry, Deborah; Sanudi, Esnart; Bellos, Mcdaphton; Hoffman, Risa M.
ABSTRACT: Background : Test and Treat has been widely adopted throughout sub-Saharan Africa, whereby all HIV-positive individuals initiate antiretroviral therapy (ART) immediately upon diagnosis and continue for life. However, clients who feel healthy may delay ART initiation, despite being eligible under new treatment guidelines. Objective : We examined health care worker (HCW) perceptions and experiences on how feeling healthy positively or negatively influences treatment initiation among HIV-positive clients in Malawi. Methods : We conducted 12 focus group discussions with 101 HCWs across six health facilities in Central Malawi. Data were analyzed through constant comparison methods using Atlas.ti7.5. Results : Feeling healthy influences perceptions of ART initiation among HIV-positive clients. HCWs described that healthy clients feel that there are few tangible benefits to immediate ART initiation, but numerous risks. Fear of stigma and unwanted disclosure, disruption of daily activities, fear of side effects, and limited knowledge about the benefits of early initiation were perceived by HCWs to deter healthy clients from initiating ART. Conclusion : Feeling healthy may exacerbate barriers to ART initiation. Strategies to reach healthy clients are needed, such as chronic care models, differentiated models of care that minimize disruptions to daily activities, and community sensitization on the benefits of early initiation.